Deformation and failure of blast-loaded metallic sandwich panels—Experimental investigations - Zhu, Feng; Zhao, Longmao; Lu, Guoxing; Wang, Zhihua (International journal of impact engineering, 2008)
Metallic sandwich panels with a cellular core such as honeycomb have the capability of dissipating considerable energy by large plastic deformation under impact/blast loading. To investigate the structural response of sandwich panels loaded by blasts, a large number of experiments have been conducted, and the experimental results are reported and discussed in this paper. Quantitative results were obtained based on the measurement in the tests by a ballistic pendulum with corresponding sensors, and then the deformation/failure modes of specimen were classified and analysed systematically. The experimental programme was designed to investigate the effects on the structural response of face-sheet and core configurations, i.e. face-sheet thickness, cell size and foil thickness of the honeycomb, and mass of charge. The experimental data were then compared with the predicted data from finite element simulations, and the results show a good agreement between the experimental and computational studies.